Reas of development of higher education and science in ukraine in the modern conditions - Popova, L. (New Collegium, 2021)
The article investigates the main reasons that hinder the development of higher education and science in Ukraine in the present conditions. Among these reasons, the author stated the following: the gap between secondary and higher education in the country, as well as higher education and scientific and technical sphere; high percentage of migration of the population of Ukraine; insufficient level of funding for research; lack of partnerships between business and higher education institutions, which as a result contributes to the imbalance of supply and demand in the labor market, etc. The author proposes the directions of development of higher education and science in Ukraine, which solves the existing problems in the field of modern higher education and science in the present conditions. Special attention is given to the need to provide universal design in education and science for low-mobility groups (in particular, people with disabilities), as well as to ensure accessibility to social infrastructure (in particular, educational and scientific institutions). It is emphasized that in the conditions of modern development of civilization, when special attention is paid to the protection of human rights and the citizen in all spheres of life, it is advisable to introduce more effective measures in the field of education and science for people with disabilities and other representatives of the low-mobility population groups. The legislative framework regulating the requirements for creating unimpeded access to social infrastructure facilities for low-mobility groups of population is analyzed. It is noted that Ukraine does not comply with these requirements, although construction in the country is quite active. It is emphasized that Ukraine, as a developed European country, also needs to take care of everyone's rights and provide accessible education and science.